Gut microbiota in colorectal cancer: a review of its influence on tumor immune surveillance and therapeutic response - Zhang, Chunlei; Wang, Yong; Cheng, Lei; Cao, Xiansheng; Liu, Chunyuan (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) poses a significant global health burden, with gut microbiota emerging as a crucial modulator of CRC pathogenesis and therapeutic outcomes. This review synthesizes current evidence on the influence of gut microbiota on tumor immune surveillance and responses to immunotherapies and chemotherapy in CRC. We highlight the role of specific microbial taxa in promoting or inhibiting tumor growth and the potential of microbiota-based biomarkers for predicting treatment efficacy. The review also discusses the implications of microbiota modulation strategies, including diet, probiotics, and fecal microbiota transplantation, for personalized CRC management. By critically evaluating the literature, we aim to provide a comprehensive understanding of the gut microbiota’s dual role in CRC and to inform future research directions in this field.